Correctional populations in the United States, 2015 - Kaeble, Danielle (Correctional Populations in the United States, 2016)
Presents statistics on persons supervised by adult correctional systems in the United States at yearend 2015, including persons supervised in the community on probation or parole and those incarcerated in state or federal prison or local jail. The report describes the size and change in the total correctional population during 2015. Appendix tables provide statistics on other correctional populations and jurisdiction-level estimates of the total correctional population by correctional status and sex for selected years.